Innover dans le champ de l’administration universitaire : quels effets sur la dynamique de l’implication professionnelle ? - Lucile Courtois (Éducation et Socialisation)
This article deals with implicational dynamics following the implementation of an innovation in the field of university administration. Our concern has been to question these dynamics set up within the framework of an action- research process starting from heterogeneous anchorages not reducible to each other but supplementary. The innovation in question sends back to the implementation of a participative and co-constructed approach allowing the professionals who are involved there to pass from a so-called status of agents to a status of co-authors of collective actions. By means of a diachronic study in two phases of data collection through interviews, we have tried to measure the potential effects of this approach on the interviewed professionals’ implicational dynamics. The results allow us to point out that professional implication expresses itself in forms of being and acting qualitatively different between one period of data collection and the other. Innovation has notably led to a strengthening of identity, a reinforced sense of control. We question whether innovation can be vector of emancipation.